영어로 진행하는 영어수업에서의 교재와 멀티미디어 사용실태 및 활용방안 연구 - 김규리; Kyu Ri Kim (중등영어교육, 2009)
The goal of this study is to investigate the use of English textbooks and multimedia in TETE in secondary school classrooms and to provide some suggestions for successful TETE. Questionnaires were administered to 111 middle and high school teachers. Of the sample, nine teachers are selected as a focus group for an interview. According to the results of the survey, most teachers showed a positive attitude towards preparing TETE. They spent relatively more time preparing materials for TETE compared with teaching English through Korean. Between female and male teachers in high school, female teachers showed a more proactive attitude compared to male teachers. Second, the majority of teachers had negative perceptions towards English textbooks currently used for TETE. Thus they used supplementary materials in addition to the textbooks. Female high school teachers thought that current textbooks were not suitable for TETE compared to female middle school teachers. Third, teachers thought that use of multimedia could be helpful in the TETE classroom, and most teachers responded that they were using multimedia in the classroom. Female teachers used multimedia more than male teachers did. Fourth, teachers wished that the current textbooks included a variety of topics that met students`` interests. Teachers also wanted ease of access to materials for effective use of multimedia. The findings of the study suggest some useful implications for making TETE productive and effective.